Jeśli spekulować to z nostalgią... Filmowe spotkania utopii literackich i architektonicznych - Stasiowski, Maciej (Er(r)go. Teoria - Literatura - Kultura, 2013)
Maciej Stasiowski Speculating with Nostalgia… Cinematic Encounters of Literary and Architectural Utopias. By confronting literary and architectural utopias the article presents the way they entered a dialogue that took place in cinema. Imagination of experimental architects was frequently based on fiction depicting perfect societies and vice-versa—literary utopias speculated on future societies shaped by daring projects of industrial revolution and modernism. The chief problem here is understood as both a specific plan—a vision of a utopian state representing a particular urban plan—and a treatise demonstrating the utopian way of thinking (Thomas Morus, H.G. Wells, Aldous Huxley.) This ideological machine directs human actions which is exemplified in film history and in the range of Utopian transformations—beginning with class stratification in Metropolis (F. Lang, 1927) which in visual terms refers to Hugh Feriss’ drawings, to ideas proposed by New Urbanism presented in Urbanized (G. Hustwit, 2011), a film demonstrating how a citizen does not have to remain a passive recipient of urban planning and resulting behavioral patterns. The question of whether Utopia anticipates or reminisces a given reality continues to be unanswered and the article explains reasons behind this aporia.